Characteristics and physicochemical properties of Kappaphycus alvarezii edible straw with the addition of tapioca flour - Nurwahyuni, Ida; Haryati, Sakinah; Surilayani, Dini; Hasanah, Afifah Nurazizatul (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
One of the biggest problems with plastic is that because of its chemical composition, it never biodegrades and never breaks down completely. Solution that can be made to reduce the amount of plastic waste is to make environmentally friendly materials, for example edible straw.. The aim of this research is to evaluate the physicochemical characteristics and obtain the best concentration of edible straw made from Kappaphycus alvarezii seaweed with the addition of tapioca flour based on hedonic organoleptic and organoleptic scoresheet assessments (appearance, aroma, taste, texture), water resistance test assessment, and proximate assessment (water content, ash content, protein content, carbohydrate content). This research method used a Completely Randomized Design (CRD) consisting of 4 treatments, the differences concentration of tapioca flour in 300 g of seaweed puree (RL1 (0 g), RL2 (50 g), RL3 (100 g), RL4 (150 g )) and done with 2 repetitions. Data were analyzed using Analysis of Variance (ANOVA) and the Mann-Whitney test at a 95% confidence interval. The addition of tapioca flour had a significant effect on Kappaphycus alvarezii seaweed edible straw (p<0.05) in the proximate test with the best treatment, which are water content 20,64%, ash content 2,01%, protein content 2,03%, fat 0,18%, carbohydrate content 75,90% and organoleptic values, such as appearance 8,07, smell 6,50, taste 4,43 and texture 7,83. The addition of tapioca flour also had a significant effect on the water resistance test which is 43,056%.